Gender Persecution of Afghan Women Under Taliban Rule: Assessing the ICC’s Jurisdiction and Responsibility - Zarafshan Hussaini (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2026)
The Taliban's return to power in Afghanistan in 2021 was one of the most severe contemporary attacks on women's and girls' rights. Since then, the Taliban rule has imposed several restrictions on every aspect of women's lives, including access to education, freedom of movement, dress, work, public life, and political participation. Women and girls were excluded from society through such measures and systems. This paper analyzes whether the Taliban’s acts against women and girls count as gender-based persecution under the Rome Statute of the International Criminal Court (ICC). Using a normative analysis of journals, case studies, books, international organization reports, and ICC jurisprudence, the study demonstrates how the Taliban’s actions constitute a systematic and widespread attack against a civilian population. It further evaluates the ICC’s jurisdiction, legal standards, and the feasibility of prosecuting the Taliban authority. The findings indicate that the Taliban’s restrictive policies meet all key elements of gender persecution under Article 7(1)(h) of the ICC, including the severe deprivation of fundamental rights, the discriminatory intent behind the policies, and the targeted nature of the attacks against women and girls. ICC route, including territorial jurisdiction for crimes committed while Afghanistan was a state party to the Rome Statute, personal jurisdiction over nationals of ICC member states, and the possibility of referral through the UN Security Council. The article concludes that recognizing the Taliban’s actions as gendered harassment is not only legally justified but also necessary to ensure accountability and strengthen international human rights support.